Exchange Rate Pass-Through to Domestic Prices : Does the Inflationary Environment Matter? - Hakura, Dalia (IMF Working Papers; Working Paper ;, 2001)
The paper tests a hypothesis suggested by Taylor (2000) that a low inflationary environment leads to a low exchange rate pass-through to domestic prices. To test this hypothesis, the paper derives a pass-through relation based on new open economy macroeconomic models. A large database that includes 1979-2000 data for 71 countries is used to estimate this relation. There is strong evidence of a positive and significant association between the pass-through and the average inflation rate across countries and periods. The inflation rate, moreover, dominates other macroeconomic variables in explaining cross-regime differences in the pass-through.